Effects of physical properties and undrained cyclic shear conditions on the pore water pressure responses of saturated sands and clays - Tran Thanh, Nhan; Matsuda, Hiroshi; Tran Thi Phuong, An; Nguyen Thi Thanh, Nhan; Pham Van, Tien; Do Quang, Thien (Vietnam Journal of Earth Sciences, 2022)
For clarifying the effects of relative density (Dr) and Atterberg’s limits on the cyclic shear-induced pore water pressure properties of soils, sandy soils with similar index properties and clayey soils with different Atteberg’s limits were collected from Vietnam and Japan and used for this study. Specimens at Dr = 50% of Nam O sand and Dr = 70% of Toyoura sand, and those of Hue clay and Japanese Kaolin clay were consolidated under the vertical stress of σvo = 49 kPa. They were then subjected to undrained cyclic shear for various cyclic shear directions and wide ranges of the number of cycles and shear strain amplitudes. Under the same cyclic shearing conditions, specimens of sand at higher Dr (Toyoura sand) and clay with higher Atterberg’s limits (Kaolin) show a lower pore water pressure ratio. The number of cycles and the cumulative shear strain at the starting point of pore water pressure generation were observed for different soils and testing conditions. In addition, using the cumulative shear strain, a new strain path parameter, the effects of shear strain amplitude and cyclic shear direction can be captured, resulting in a unique uacc/σ’vo - G*  relation on each soil. Based on this, fitting lines can be drawn and referred to promote a prediction of the cyclic shear-induced pore water pressure accumulation for the used soils under different cyclic shear conditions.